2002
DOI: 10.1159/000047001
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline Hydrochloride Treatment for Patients with Hemodialysis Hypotension

Abstract: Background: Recently some pathogenetic parallels have been drawn between dialysis-induced hypotension and disorders characterized by hemodynamic instability due to autonomic dysfunction, such as neurocardiogenic syncope and idiopathic orthostatic hypotension. Several studies have shown that central serotonergic pathways participate in the abnormal response, and selective serotonin reuptake inhibitors improve the symptoms of patients with neurocardiogenic syncope or idiopathic orthostatic hypotension. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
2
22
1
Order By: Relevance
“…The data of this study supported the result of our previous study and confirmed that sertraline, after a 4-week course of treatment, effectively prevents DIH in patients with episodes of symptomatic DIH in more than 50% of HD treatments [21]. Optimum dry weights and cardiac status of these patients were well evaluated to exclude excess UF and cardiac diseases.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The data of this study supported the result of our previous study and confirmed that sertraline, after a 4-week course of treatment, effectively prevents DIH in patients with episodes of symptomatic DIH in more than 50% of HD treatments [21]. Optimum dry weights and cardiac status of these patients were well evaluated to exclude excess UF and cardiac diseases.…”
Section: Discussionsupporting
confidence: 89%
“…However, most of these drugs have been modestly effective or poorly tolerated [26]. Our studies demonstrate that sertraline is a useful alternative to prevent DIH in the patients having hypotension despite institution of the dialysate with high sodium and cool temperature [21]. Sertraline hydrochloride, a selective central serotonin re-uptake inhibitor, is a well-known antidepressant drug and it can be used in the patients with end-stage renal failure without dose reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of depression in hemodialysis patients with fluoxetine appears safe, yielding fluoxetine and norfluoxetine blood levels comparable to those of patients with normal renal function (Blumenfield et al, 1997;Levy et al, 1996), and more effective than placebo in the treatment of depression (Blumenfield et al, 1997). In fact, the fluoxetine and sertraline may also be beneficial with regard to alleviating postural hypotension in dialysis patients, present in up to 50% of patients with end-stage renal disease (Chin et al, 1996;Yalcin et al, 2002). The use of citalopram for the treatment of depression in patients with hepatitis C also appears not to reduce levels of aspartate aminotransferase, alanine aminotransferase, or γ-glutamyltransferase (Gleason et al, 2002).…”
Section: Safety: the Use Of Ssris In Various Medical Conditionsmentioning
confidence: 99%